Path analysis of influencing factors for anxiety and depression among first-trimester pregnant women - Li, Wenjuan; Lin, Leshi; Teng, Sheng; Yang, Yi; Li, Li; Peng, Fang; Peng, Dongmei; Gao, Xiao; Huang, Guojun (Frontiers in Psychology, 2024)
Background: Prenatal anxiety and depression exert a significant influence on the physiological and psychological health outcomes of both expectant mothers and their infants. The aim of this study was to explore the intrinsic relationships between maternal anxiety, depression in early pregnancy, and their influencing factors. The findings of this study provide scientific basis for developing targeted preventive interventions. Methods: The study involved 887 expectant mothers in the early stages of pregnancy residing in Changsha City from March to August 2022. The sociodemographic characteristics, health and lifestyle factors, and pregnancy-related factors of participants were collected. The Edinburgh Postnatal Depression Scale and the Self-Rating Anxiety Scale were used to assess depression and anxiety, respectively. Chi-square tests and multivariate logistic regression models using SPSS 26.0 were used to assess factors impacting early pregnancy anxiety and depression. Amos 23.0 was used to construct a path model to determine the potential pathways of the influencing factors. Results: In early pregnancy, the prevalence of depression and anxiety were 17.4% and 15.8%, respectively. Path analysis showed that early pregnancy anxiety and illness during pregnancy had a direct effect on early pregnancy depression. Anxiety had the greatest overall impact on early pregnancy depression. Education, maternal comorbidities, symptoms of pregnancy, electronic device usage time, work stress, active smoking in the 6 months before pregnancy, and sleep quality were found to solely exert indirect effects on early pregnancy depression. Sleep quality had the greatest overall impact on early pregnancy anxiety. Active smoking in the 6 months before pregnancy, sleep quality, and work stress only had a direct impact on early pregnancy anxiety. Additionally, electronic device usage duration and monthly per capita household income exclusively indirectly impacted symptoms of early pregnancy anxiety. Conclusions: The study highlights the importance of targeted interventions in early screening. Avoiding excessive use of electronic devices and active smoking in the 6 months before pregnancy, alleviating work stress and symptoms of pregnancy, increasing education levels and monthly per capita household income, improving sleep quality, and actively preventing illnesses during pregnancy and maternal comorbidities might reduce anxiety and depression in early pregnancy.